2007
DOI: 10.1021/ef700398f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Relative Bed Lengths on a Platinum/Nickel Stratified Dual Bed Catalyst for the Catalytic Partial Oxidation of Methane at Millisecond Contact Times

Abstract: Stratified, dual bed catalysts composed of platinum followed by nickel have shown reactant conversions and product selectivities similar to rhodium, which has shown the highest activity for the millisecond catalytic partial oxidation reaction. The goal of the stratified catalyst is to carry out the catalytic partial oxidation in a two-step process: combustion catalyzed by platinum followed by steam and carbon dioxide reforming catalyzed by nickel. Previous studies have shown that sequential platinum and nickel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 14 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Indeed, noble metals, mainly Pt [12,15] and Rh [16,30], are usually the active species; although the use of bimetallic noble metal-nickel or cobalt catalysts [31] and stratified beds [32] are also reported. The amount of active species, which modifies the thermal profile [8,16,26], may be controlled by pore size [33], layer thickness [34] , and metal loading [30].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, noble metals, mainly Pt [12,15] and Rh [16,30], are usually the active species; although the use of bimetallic noble metal-nickel or cobalt catalysts [31] and stratified beds [32] are also reported. The amount of active species, which modifies the thermal profile [8,16,26], may be controlled by pore size [33], layer thickness [34] , and metal loading [30].…”
Section: Introductionmentioning
confidence: 99%
“…Each point on a plot represents the average of three separate experimental runs. Under similar analysis conditions, Bell and Leclerc [15] found that the uncertainty in the methane conversion and carbon selectivities was 0.5%, while the uncertainty in the hydrogen selectivities was 2%.…”
Section: Reactor Set-upmentioning
confidence: 87%
“…Optimization should boost the yield of the silicasupported catalyst over that of ethylene. Bell et al 15 have shown that for a similar reactor system analyzed by gas chromatography, conversions and selectivities have an uncertainty of only 0.5%. The small changes in reactor performance as measured by gas chromatography in these experiments are in fact statistically significant.…”
Section: Articlementioning
confidence: 99%